Perspectives On Digitization And Economic Growth In India (Journal of Namibian Studies : History Politics Culture, 2024)
This study examines digitization and its effect on various sectors of the Indianeconomy. India's digital transformation has been remarkable in recent years, with the rapid adoption of smartphones, increased internet connectivity, and the government's push towards a digital economy. It has opened tremendous opportunities for economic growth across various sectors of the economy. The fast-paced digitization has significantly impacted the country's economic growth, with tremendous opportunities for continued growth in the digital economy. India has witnessed a remarkable increase in internet penetration, primarily driven by affordable smartphones and data plans. The number of internet users in India surpassed 600 million by the end of 2020, and this number is expected to continue to grow rapidly. With the government's continued focus on digital transformation and investments in digital technologies, India is well-positioned to continue to drive economic growth. Digital technologies such as data pooling, artificial intelligence, and others are now widely used to track and diagnose issues in agriculture; health; environment; logistics; jobs; skills market; e-governance; performing daily tasks such as navigating traffic, paying bills; and financial transactions, among others. The study employs secondary data extracted from various literature sources to analyze the impact of digitization on India’s economic growth. It also involves a systematic review of the literature on the digital economy and economic reforms issues to address the objective. The research is particularly important for researchers and policymakers and offers opportunities for future studies.